Proboscis lateralis: A rare case report and brief literature review - Hisham Alshwaikh; Yasser ALGhabra; Ahmad Kammasha; MHD Mohannad Oyoun; Hala Alibrahim; Abdulmajeed Yousfan (Acta Oto-Laryngologica Case Reports, 2025)
Proboscis lateralis (PL) is an exceedingly rare congenital craniofacial malformation characterized by a trunk-like appendage near the medial canthus. This report presents the first documented case of PL in Syria and, to our best knowledge, the broader Middle East region. The case is particularly notable for occurring in the absence of parental consanguinity, adding to its uniqueness. A 25-day-old female neonate presented with a 2.5 cm tubular structure at the right medial canthus, accompanied by right nasal cavity hypoplasia and nasal septum deviation. These findings were confirmed by CT imaging. Surgical intervention was suspended. PL arises from the disrupted fusion of the frontonasal and maxillary processes and is typically diagnosed clinically, though prenatal identification remains rare. Associated anomalies, including intracranial defects, necessitate imaging modalities such as CT or MRI for comprehensive evaluation. Surgical strategies vary depending on anatomical complexity, emphasizing the need for individualized approaches.